Patron-driven acquisition: perception on e-book selection practices at academic libraries in Malaysia / Norliya Ahmad Kassim and Che Zainab Hj Abdullah - Kassim, Norliya Ahmad; Hj Abdullah, Che Zainab (Research Management Institute (RMI), 2012)
Library is the core business of higher institution. The acquisition department in the library, act as catalyst in selecting and providing information resources for university in achieving its mission and vision. In most academic libraries in Malaysia, the selection of e-books is done by the collection development officer. These phenomena lead to a situation whereby the titles selected are not being borrowed by the customers. To avoid the uneconomical situation, the academic libraries must develop relevant e-book collection policies based on the users' needs. The purpose of this study is to find out the perception on the current practices of collection development policy of e-book at academic libraries in Malaysia. The specific objectives are: (1) to ascertain the practice of e-book selection practices among academic libraries in Malaysia, and (2) to determine the Return on Investment (ROI) regarding e-book selection practices among academic libraries in Malaysia. To achieve the objectives of this study, the researcher considered the appropriateness of using the quantitative method. A survey using questionnaire is used as the instrument to collect data. A semi-structured interview is conducted in the initial stage of the study to explore background information and to help with the development of the instrument. The population for the study comprises of all professional librarians in the acquisition department at the academic libraries in Malaysia as listed in the directory of Malaysian University libraries' website. Statistical Package & Service Solution (SPSS) Version 17.0 is used for data analysis. The findings of the study will produce a guideline in the selection of e-book libraries in Malaysia.